Ratio of roughage to concentrate for fattening beef cattle-Summary - Richardson, D.; Smith, E.F.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
Four tests, one with steer calves and three with heifers, were conducted to study the ratio of roughage to concentrate in beef cattle fattening rations. Beef cattle are naturally large consumers of roughage and serve as one of the principal means of marketing this product. Since a large amount of roughage normally is produced in Kansas, it is desirable to have information concerning the maximum roughage that can be used in fattening rations, consistent with maximum production and economical gains which, at the same time, produces the kind of carcass desired. This information should help plan the best way to use one's available feed supply.
Keywords: Beef; Roughage; Concentrates